2022
DOI: 10.1016/j.jsxm.2022.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prostate Artery Embolization on Erectile Function – A Single Center Experience of 167 Patients

Abstract: Background Prostate artery embolization (PAE) is an emerging therapy for lower urinary tract symptoms (LUTS) associated with benign prostatic hyperplasia (BPH). Aim This retrospective study was conducted to assess the effect of prostate artery embolization (PAE) on erectile function in a cohort of patients with LUTS attributable to BPH at 3-months after the procedure. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…45 The risk of urethral stricture and incontinence is also present after transurethral procedures but are not seen after PAE. Erectile dysfunction can be seen in transurethral procedures, but interestingly some studies have shown slight improvement in erectile function 46 and no reports have shown any negative impact on erectile function after PAE. Bleeding requiring transfusion is reported in 2.5% of patients in large TURP series, but this is not reported after PAE.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…45 The risk of urethral stricture and incontinence is also present after transurethral procedures but are not seen after PAE. Erectile dysfunction can be seen in transurethral procedures, but interestingly some studies have shown slight improvement in erectile function 46 and no reports have shown any negative impact on erectile function after PAE. Bleeding requiring transfusion is reported in 2.5% of patients in large TURP series, but this is not reported after PAE.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…135,136 Eine im Jahr 2022 veröffentlichte Studie bestätigt diese Aussage. 137 QoL-Score >3 oder >4 betrug in der Auswertung berücksichtigt. 78,131 Die präinterventionelle MRA bringt laut der hier vorliegenden Analyse keinen Mehrwert hinsichtlich des Erhalts der sexuellen Funktion und für die Lebensqualität.…”
Section: Abb 24: Punktediagramm Mit Darstellung Der Höchst Signifikan...unclassified